A study on the effect of oral hypoglycaemic agents on arterial stiffness among malay patients with type 2 diabetes mellitus - Hassan, Noor Hasliza (2006)
Objective : The purpose of this study is to see whether there was any significant difference in arterial stiffness (as measured by augmentation index) between diabetic and non diabetic subjects and to see whether there was any significant difference between two different oral hypoglycaemic agents(OHA) regimens, (sulphonylurea monotherapy and metformin in combination with sulphonylurea therapy) on arterial stiffness. Methods : This was a case control study conducted in the Klinik rawatan keluarga(KRK) and Diabetic clinic, HUSM from May 2004 till May 2005. Hundred and two diabetic subjects and hundred and two age- and sex-matched non-diabetic control subjects were recruited after obtaining verbal consent following explanation of study protocol. Augmentation index (AI) was measured using the Sphygmocor apparatus and all measurements were performed by the researcher after an earlier validation study. These mean augmentation index measurements were then analyzed. Result : The mean of AI of diabetic subjects was significantly higher than non diabetic subjects ( 140.32 ± 12.0% Vs 128.77 ± 10.69%, P < 0.0001 ). However, therewas no significant difference in mean AI between two different OHA regimen groups in diabetic subjects (140.51 ± 11.42 Vs 140.14 ± 12.86, 95% CI: -4.40, 5.15, p = 0.877). Conclusion: Diabetic patients have increased arterial stiffness compared with age- and sex-matched non diabetic subjects, which may partly explain why diabetes mellitus are associated with increased cardiovascular risk. This study also showed that two different groups of oral hypoglycaemic agents have no effect in relation to arterial stiffness.